La sculpture sur le bout des doigts. Retour sur l’élaboration d’une salle pédagogique et tactile au musée Bourdelle - Colin Lemoine; Amélie Simier (Les Cahiers de l'École du Louvre)
How is a sculpture born? A sculpture is not the work of a single hand. Besides the artist, many are the assistants working in the shadows. Old photographs show Bourdelle’s workshop filled with collaborators that refute the myth of the solitary artist, working far away from everyone and everything. In clay, plaster, bronze or marble, a sculpture crystallises several skills, multiple professions and countless tools. Inaugurated in spring 2013, and installed in the former studio of the painter Eugène Carrière (1849-1906), the educational room of the Musée Bourdelle explains the complex and plural history of the making of a sculpture. Strong with contemporary or past experiences, the space is born of the desire to help – all publics – understand, see and touch what constitutes a sculpture. The article with two authors will explain the birth and audience of this project.